Partisan politics and economic intervention: evidence from an aggregating approach - Engler, Fabian; Jathe, Jan; Zohlnhöfer, Reimut (West European politics, 2024)
While government intervention in the economy has decreased in recent decades, the literature disagrees on the causes of this development. This article provides a comprehensive picture by aggregating five economic policy instruments (regulation, state ownership, business taxation, subsidisation, government spending) into one index for 20 OECD countries between 1981 and 2018. It studies partisan politics and the conditioning effects of domestic and international economic pressures (unemployment, globalisation). It is argued that the moderating effect varies for short- and long-term pressures for domestic, but not for international factors. Regression analyses highlight the role of political parties with the left increasing intervention. Moreover, partisan differences are particularly relevant when unemployment is high, but disappear as unemployment increases. Regarding globalisation, partisan differences decrease with the level of globalisation, while short-term changes do not condition them. This aggregating approach sheds new light on partisan politics when it comes to state intervention in the economy.